Integrating Philips' extreme UV source in the alpha-tools - Pankert, J; Apetz, R; Bergmann, K; Derra, G; Janssen, M; Jonkers, J; Klein, J; Krucken, T; List, A; Loeken, M; Metzmacher, C; Neff, W; et al. (2005)
The paper describes recent progress in the development of the Philips's EUV source. Progress has been realized at many frontiers: Integration studies of the source into a scanner have primarily been studied on the Xe source because it has a high degree of maturity. We report on integration with a collector, associated collector lifetime and optical characteristics. Collector lifetime in excess of 1 bln shots could be demonstrated. Next, an active dose control system was developed and tested on the Xe lamp. Resulting dose stability data are less than 0.2% for an exposure window of 100 pulses. The second part of the paper reports on progress in the development of the Philips' Sri source. First, the details of the concept are described. It is based on a Laser triggered vacuum arc, which is an extension with respect to previous designs. The source is furbished with rotating electrodes that are covered with a Sri film that is constantly regenerated. Hence by the very design of the source, it is scalable to very high power levels, and moreover has fundamentally solved the notorious problem of electrode erosion. Power values of 260 W in 2 pi sr are reported, along with a stable, long life operation of the lamp. The paper also addresses the problem of debris generation and mitigation of the Sn-source. The problem is attacked by a combined strategy of protection of the collector by traditional means (e.g. fields, foiltraps,...), and by designing the gas atmosphere according to the principles of the well known halogen cycles in incandescent lamps. These principles have been studied in the Lighting industry for decades and rely on the excessively high vapor pressures of metal halides. Transferred to the Sri source, it allows pumping away tin residues that would otherwise irreversibly deposit on the collector.